(untitled) (Eurasian Scientific Herald, 2023)
The world experience of socio-economic development of states and their territories, including villages, is a clear evidence and confirmation of the high importance and role of the small business sector in society in ensuring socio-economic development and sociopolitical stability. In almost all economically developed countries of the world, this sector represents the middle class, which is the basis for the sustainable development of the entire national economy and the economy at the local level, because it is the leading segment that contributes to the supply of goods and services to the market, the creation of new jobs and the reduction of unemployment.